Trends in methodological and theoretical orientations in contemporary political communication research (2017)
This study appraised the methodological and theoretical approaches commonly employed in political communication studies. It adopted content analysis as a research method to examine 160 political communication-related articles in reputable peer-reviewed journals published between 2005 and 2015. It was found that, overall, political communication researchers seldom employed mixed methods (6.3%), while they seemed to prefer quantitative designs (75.0%) to qualitative approaches (18.8%). Specifically, researchers employed survey (43.3%) and content analysis (35.4%) more frequently than other methods. They used interviews (39.4%) and case studies (27.3%) more frequently than other qualitative methods. Also, the study reveals that in political communication studies, application of theories has gained prominence with the framing and the agenda-setting theories topping the list of commonly used theories. The trends here suggest frequent use of theories, but extreme paradigmatic preference among political communication scholars with few cases of quantitative qualitative complementarity. The study, therefore, concludes that copious use of theories to drive studies is a positive trend, but political communication researchers should be encouraged to be pragmatic and embrace mixed methods because a single methodological approach may not always be adequate in solving most research problems.